9514 1404 393
Answer:
as written: (12√6)a²
Explanation:
The way you have written this, only the numbers are under the radicals:
![√(18)a^2\cdot4√(3)a^2=4√(18\cdot3)a^(2+2)=4√(3^2\cdot6)a^4\\\\=\boxed{12√(6)\cdot a^4}](https://img.qammunity.org/2022/formulas/mathematics/college/7fzvo6mr93knzfitvdpf7r3sbc464dquo7.png)
__
We suspect you may want to simplify ...
![√(18a^2)\cdot4√(3a^2)=4√(54a^4)=4√(6(3a^2)^2)=\boxed{12√(6)\cdot a^2}](https://img.qammunity.org/2022/formulas/mathematics/college/ebpk9kjkxkikzqna666k00xi2jeo6wxl42.png)
_____
We make use of the rules for combining radicals and exponents.
(√a)(√b) = √(ab)
(a^b)(a^c) = a^(b+c)
√(a²) = a . . . . for a ≥ 0